Answer:
Hey There!! The answer to this is: 2(3x+16) Identify the expression equivalent to 4(x + x + 7) − 2x + 8 − 4
4(x + x + 7) − 2x + 8 − 4
When x=1 , the expression becomes 4(1+1+7)-2(1)+8-4=38
When x=2 , the expression becomes 4(2+2+7)-2(1)+8-4=44
Plug in x=1 and check with each expression
6x + 11 =6(1) +11= 16
3(x + 7) = 3(1+7)= 3(8)= 24
2(3x + 16) = 2(3(1)+16)= 38 , we got same answer when x=1, now check with x=2
2(3x + 16) = 2(3(2)+16)= 44
Thus, for 3x + 16= 3+16= 19.
Hope It Helped!~ ♡
ItsNobody~ ☆